Placental Amniotic Epithelial Cells and Their Therapeutic Potential in Liver Diseases - Tahan, Asli Ceren; Tahan, Veysel (Frontiers in Medicine, 2014)
As a unique source of stem cells, there is a growing interest in amniotic epithelial (AE) cells. Placenta is readily available; in fact, it is often discarded following delivery. As such, it is without the ethical concerns of embryonic stem cells. Further advantages to AE include that AE cells do not demonstrate tumorigenicity upon transplantation, and are gifted with immunomodulatory and anti-inflamatory properties. Thus, AE cells have exceptional features for use as cell-based therapies for liver disease.